Unveiling Syntactical Errors in SHS Students - Contreras, Clarise Tan (JETAL: Journal of English Teaching & Applied Linguistic, 2024)
Academic writing has always been one of the hardest skills to develop as it requires mastery of the language. With the unforeseen pandemic, developing the said skills of the learners in this generation has become harder as new modes of instruction that are unfamiliar to both teachers and students emerge. With that, the main focus of this study is to identify the types and frequency of errors the students commit in writing academic papers in an attempt to provide the best possible interventions to remediate them. To achieve these objectives, 15 position papers were collected and analyzed. Error analysis designed by Gass and Selinker in 2008 was applied. In the end, results have been tabulated in descending sequence in which grammar appeared as the most frequent error. Strategies, such as the use of AI in checking grammar, and interventions, such as giving feedback and drafting, are recommended.